Non-Markovianity hinders Quantum Darwinism - Fernando Galve; Roberta Zambrini; Sabrina Maniscalco (NATURE PUBLISHING GROUP, 2022)
We investigate Quantum Darwinism and the emergence of a classical world from the quantum one in connection with the spectral properties of the environment. We use a microscopic model of quantum environment in which, by changing a simple system parameter, we can modify the information back flow from environment into the system, and therefore its non-Markovian character. We show that the presence of memory effects hinders the emergence of classical objective reality, linking these two apparently unrelated concepts via a unique dynamical feature related to decoherence factors.